Change in effectiveness of sotrovimab for preventing hospitalization and mortality for at-risk COVID-19 outpatients during an Omicron BA.1 and BA.1.1-predominant phase. (March 2023) - Aggarwal, Neil R.; Beaty, Laurel E.; Bennett, Tellen D.; Carlson, Nichole E.; Mayer, David A.; Molina, Kyle C.; Peers, Jennifer L.; Russell, Seth; Wynia, Matthew K.; Ginde, Adit A.
Highlights: Adult outpatients infected with Omicron BA.1 or BA.1.1 were administered sotrovimab. Sotrovimab did not reduce hospitalization compared to all untreated patients. Sotrovimab may reduce hospitalization rates in the highest-risk outpatient subgroups. Sotrovimab treatment benefit during Delta was markedly attenuated in Omicron BA.1. ABSTRACT: Objectives: Sotrovimab effectively prevented progression to severe disease and mortality following infection with pre-Omicron SARS-CoV-2 variants. We sought to determine whether sotrovimab is similarly effective against SARS-CoV-2 Omicron variant infection. Methods: Observational cohort study of non-hospitalized adult patients with SARS-CoV-2 infection from December 26, 2021, to March 10, 2022, using electronic health records from a statewide health system. We propensity-matched patients not receiving authorized treatment for each patient treated with sotrovimab. The primary outcome was 28-day hospitalization; secondary outcomes included mortality. We also propensity-matched sotrovimab-treated patients from the Omicron and Delta phases. Logistic regression was used to determine sotrovimab effectiveness during Omicron and between variant phases. Results: Of 30, 247 SARS-CoV-2 Omicron variant infected outpatients, we matched 1542 receiving sotrovimab to 3663 not receiving treatment. Sotrovimab treatment was not associated with reduced odds of 28-day hospitalization (2.5% vs 3.2%; adjusted odds ratio [OR] 0.82, 95% CI 0.55, 1.19) or mortality (0.1% vs 0.2%; adjusted OR 0.62, 95% CI 0.07, 2.78). Between phases, the observed treatment OR was higher during Omicron than during Delta (OR 0.85 vs 0.39, respectively; interaction P -value = 0.053). Conclusion: Real-world evidence demonstrated that sotrovimab was not associated with reduced 28-day hospitalization or mortality among COVID-19 outpatients during the Omicron BA.1 phase.